EVALUASI KINERJA KERUSAKAN JALAN MENGGUNAKAN METODE BINA MARGA - Kiradi Kiradi; Muhammad Idham (LPPM Universitas Abdurrab, 2024)
Roads are the main access for the people of the city of Dumai to carry out transportation activities in life, so that the presence of roads can increase the economy and social activities for the people, especially the people of the city of Dumia. The performance of the Cut Nyak Dien road is greatly influenced by the condition of the road surface, many of the Cut Nyak Dien roads experience damage before reaching the planned age. Therefore, this research can identify the damage to the Cut Nyak Dien road in the city of Dumai, Purnama sub-district using the Bina Marga method through the calculation of the Surface Distress Index (SDI). From the results of the study, it was shown that the road damage found on Jalan Cut Nyak Dien deer were cracks, holes, patches and settlements, so the results of the calculation of the Surface Distress Index (SDI) showed that on Jalan Cut Nyak Dien an average value of 10 belonged to routine maintenance. on that road. Keywords: Road Damage, Bina Marga, RCS, RCI, SDI